2019
DOI: 10.1002/ece3.5945
|View full text |Cite
|
Sign up to set email alerts
|

N‐P utilization ofAcer monoleaves at different life history stages across altitudinal gradients

Abstract: The relationship between plants and the environment is a core area of research in ecology. Owing to differences in plant sensitivity to the environment at different life history stages, the adaptive strategies of plants are a cumulative result of both their life history and environment. Previous research on plant adaptation strategies has focused on adult plants, neglecting saplings or seedlings, which are more sensitive to the environment and largely affect the growth strategy of subsequent life stages. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…This may be because pseudohalophytes increase their salt tolerance through the compensatory growth of roots [3], and reduced C content is transported up leaves by pseudohalophytes; thus, leaf C was positively correlated with soil C. There was no significant difference in soil N and P contents among the different functional groups of halophyte shrubs, but the utilization and consumption strategies of nutrient elements in different functional groups of halophyte shrubs were different [30]. This indicates that the ecological stoichiometric characteristics of desert saline shrub leaves are not directly determined by the characteristics of soil nutrient contents, but are related to their own genetic characteristics, which reflects the unique adaptation mechanism of different desert halophyte shrubs to habitats [50], consistent with the results of Luo et al (2017) [51] and Song et al (2020) [52]. Under soil moisture-and nutrient-scarce conditions, Xinjiang desert halophyte shrubs have formed their own unique stoichiometric characteristics and physiological ecology, reflecting the relatively stable adaptability of desert saline shrubs to extreme environments [16].…”
Section: Response Of Desert Halophyte Shrubs' Stoichiometry To Soil F...supporting
confidence: 79%
“…This may be because pseudohalophytes increase their salt tolerance through the compensatory growth of roots [3], and reduced C content is transported up leaves by pseudohalophytes; thus, leaf C was positively correlated with soil C. There was no significant difference in soil N and P contents among the different functional groups of halophyte shrubs, but the utilization and consumption strategies of nutrient elements in different functional groups of halophyte shrubs were different [30]. This indicates that the ecological stoichiometric characteristics of desert saline shrub leaves are not directly determined by the characteristics of soil nutrient contents, but are related to their own genetic characteristics, which reflects the unique adaptation mechanism of different desert halophyte shrubs to habitats [50], consistent with the results of Luo et al (2017) [51] and Song et al (2020) [52]. Under soil moisture-and nutrient-scarce conditions, Xinjiang desert halophyte shrubs have formed their own unique stoichiometric characteristics and physiological ecology, reflecting the relatively stable adaptability of desert saline shrubs to extreme environments [16].…”
Section: Response Of Desert Halophyte Shrubs' Stoichiometry To Soil F...supporting
confidence: 79%
“…Some studies have also found that N does not change with tree height or age (Day et al 2001;Niinemets 2002). P showed a significant downward trend with increasing ontogenetic stage; this finding is surprising because it seems to be inconsistent with previous observations (Palow and Kitajima 2012;Song et al 2019). This may be the result of tree size altering the pattern of P allocation (Niinemets and Kull 2003).…”
Section: Variation In Leaf Traits With Ontogenetic Stagementioning
confidence: 70%
“…The standardized major axis method was used to explore the effects of ontogenetic stage and leaf age on trait-trait relationships. We found that LMA and LDMC increased significantly and N and P decreased significantly 1 2013; Damián et al 2018;Song et al 2019). Thus, tree age or ontogenetic stage may be an important cause of trait variation (Steppe et al 2011;Kuusk et al 2018).…”
Section: Introductionmentioning
confidence: 68%
“…In most studies, leaf maturity affected carbon access and allocation, leading to differences in carbohydrate content (Damian et al, 2018; Zhang et al, 2018; Song et al, 2020). The SEM results showed that leaf maturity had a significant positive effect on carbohydrate content, suggesting that the accumulation of carbohydrates was positively related to leaf senescence.…”
Section: Discussionmentioning
confidence: 99%